Reversing Adhesion: A Triggered Release Self‐Reporting Adhesive. Issue 3 (2nd February 2016) - Schenzel, Alexander M.; Klein, Christopher; Rist, Kai; Moszner, Norbert; Barner‐Kowollik, Christopher
Abstract : Here, the development of an adhesive is reported – generated via free radical polymerization – which can be degraded upon thermal impact within minutes. The degradation is based on a stimuli responsive moiety (SRM) that is incorporated into the network. The selected SRM is a hetero Diels‐Alder (HDA) moiety that features three key properties. First, the adhesive can be degraded at relatively low temperatures (≈80 °C), second the degradation occurs very rapidly (less than 3 min), and third, the degradation of the network can readily be analyzed and quantified due to its self‐reporting nature. The new reversible self‐reporting adhesion system is characterized in detail starting from molecular studies of the retro HDA reaction. Moreover, the mechanical properties of the network, as well as the adhesion forces, are investigated in detail and compared to common methacrylate‐based systems, demonstrating a significant decrease in mechanic stability at elevated temperatures. The current study thus represents a significant advance of the current state of the art for debonding on demand adhesives, making the system interesting for several fields of application including dental adhesives. Abstract : A novel adhesive, generated via free radical polymerization, that can be degraded upon thermal impact (≈80 °C) within minutes, is presented. The degradation is based on a stimuli responsive moiety (SRM) that is incorporated into the network. Moreover, the degradation of the network can readily be analyzed and quantified due to the self‐reporting nature of the SRM.